"Just a Joke": Young Australian understandings of racism. (July 2015) - Grigg, Kaine; Manderson, Lenore
Abstract: Lay understandings reflect the lived experience of racism, and our knowledge of these considerations assist with enhancing an appreciation of intergroup relations. Drawing on data from semi-structured interviews and focus groups with 30 school attendees from diverse backgrounds aged 14–22 years, conducted from December 2011 to January 2012 in Victoria, Australia, we critically examined their understandings of and experiences with racism. Data demonstrate the ambiguity of racism, while confirming that Australian youth from various racial, ethnic, cultural, and religious backgrounds consistently conceptualise, explain, and classify racism, whilst minimising some forms of racism, including racist humour. Participants described racism through three primary domains: (a) Group versus Individual: racism stems from perceived differences, with individuals stereotyped as belonging to larger groups; (b) Actions versus Beliefs: individuals are classified as racist or non-racist according to their actions and beliefs; and (c) Exceptions, Exclusions and Minimisation: racism is frequently excused and minimised. The present research highlights the need for additional exploration of the nuances of racism in Australia from lay perspectives and provides clear evidence of the need to address racism in Australian society. Further developing the evidence base to understand the lived experience of racism in Australia could inform and support the design and evaluation of anti-racism and pro-diversity initiatives. Moreover, we hope that the present data can be drawn upon to enlighten the development of instruments to more accurately measure racist attitudes in Australian youth.